Stages and principles of development of the benchmarking concept - Sklyarenko, M. G.; Pererva, P. G. (Вінницький національний технічний університет, 2023)
The stages of the development of benchmarking and the principles of its use in economic activity and enterprises are considered. Factors of the effectiveness of the use of benchmarking in business and in the formation of competitive advantages of enterprises are determined.
Етапи та принципи розробки концепції бенчмаркінгу
Keywords: вenchmarking; stages; development; principles; efficiency; competitiveness; business